2020
DOI: 10.1123/jsr.2018-0178
|View full text |Cite
|
Sign up to set email alerts
|

Static Stretching Intensity Does Not Influence Acute Range of Motion, Passive Torque, and Muscle Architecture

Abstract: Context: Although stretching exercises are commonly used in clinical and athletic practice, there is a lack of evidence regarding the methodological variables that guide the prescription of stretching programs, such as intensity. Objective: To investigate the acute effects of different stretching intensities on the range of motion (ROM), passive torque, and muscle architecture. Design: Two-group pretest–posttest design. Setting: Laboratory. Participants: Twenty untrained men were allocated into the low- or hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Previous studies have reported that higher-intensity SS affects ROM changes and muscle-tendon stiffness when compared within same subjects [9,11]. On the other hand, as described above, no significant difference was observed between ROM changes and stretching intensity when compared between each subject [10]. Therefore, it was hypothesized that a higher relative intensity of SS is more effective in inducing changes in ROM and passive properties, but absolute intensity of SS might not be related to changes in ROM and passive properties.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Previous studies have reported that higher-intensity SS affects ROM changes and muscle-tendon stiffness when compared within same subjects [9,11]. On the other hand, as described above, no significant difference was observed between ROM changes and stretching intensity when compared between each subject [10]. Therefore, it was hypothesized that a higher relative intensity of SS is more effective in inducing changes in ROM and passive properties, but absolute intensity of SS might not be related to changes in ROM and passive properties.…”
Section: Introductionmentioning
confidence: 57%
“…A previous study has reported that 120% ROM stretching intensity affects ROM and the passive properties compared to 100% ROM stretching intensity for the same subjects, i.e., relative intensity. Conversely, a previous study has reported that there is no significant difference in ROM change between the stretching intensity defined as the angle when high or low sensation of stretching felt for each subjects as the stretching intensity [10]. Therefore, it is possible that the difference in setting stretching intensity could influence the effects of SS on ROM and passive property.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The stress of static stretching increases with stretching duration and intensity. Santos et al (2020) reported that the muscle-tendon unit stiffness of the hamstrings did not change after 3-min of high-intensity static stretching at the intensity of the numerical rating scale (NRS) Levels 9–10 (an NRS of Level 10 indicates the worst possible discomfort). On the other hand, Kataura et al (2017) showed that 3-min of static stretching at the intensity of 120% ROM (NRS Level 5) effectively decreased the muscle-tendon unit stiffness of the hamstrings.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Stretching techniques include static (active or passive), dynamic, or proprioceptive neuromuscular facilitation (PNF), all of which can improve ROM. [1,[17][18][19][20] However, reduced ROM and muscle weakness are deeply associated. [21][22][23] Therefore, although strength training (ST) primarily addresses muscle weakness through methods such as resistance training or similar protocols, it has been shown to increase ROM in athletic populations, [24,25] as well as in healthy elderly people [26] and women with chronic nonspecific neck pain.…”
Section: Introductionmentioning
confidence: 99%